Moral Economy and the Agency of Independent Fishermen on the Coast of Ujung Baji Village, Takalar Regency - Sayful, M.; Muzakkir, Abd. Kahar (CV. Social Politic Genius (SIGn), 2024)
Maritime anthropological studies in Indonesia have historically focused on the dependency narrative of fishermen within the patron-client (punggawa-sawi) structure. Challenging this deterministic view, this study analyzes the emergence of independent fishermen on the coast of Ujung Baji Village, Takalar Regency, South Sulawesi, as a phenomenon of moral resistance and social praxis. This research employs an intensive ethnographic method conducted in Ujung Baji Village. Its purpose is to deconstruct the driving factors, construction processes, and implications of fishermen’s independence. The findings show that the choice to become independent is not driven solely by economic calculation, but by a crisis of moral legitimacy in the patronage system, which is perceived as having betrayed its social contract. This independence is constructed through the fishermen’s reflexive agency, manifested in concrete practices such as gaining control over the means of production and reconfiguring the household into an autonomous production unit. Supported by internal solidarity and horizontal social networks, these everyday practices cumulatively give rise to an alternative social order, transforming survival strategies into a new, dignity-rooted identity. By integrating Scott’s moral economy theory and Giddens’s structuration theory, this study concludes that independent fishermen are not an anomaly but a reflection of the birth of a new social structure from below, one that fundamentally corrects the singular narrative of coastal society.